Prolonged incubation period in neonatal Pasteurella multocida meningitis and bacteremia. Issue 6 (18th December 2014) - Yamaguchi, Hiroshi; Tamura, Takuya; Abe, Michiko; Ogiwara, Shigetoshi; Sai, Shuji; Kosugiyama, Kiyotaka; Sugihara, Akemi; Nagumo, Kiyoshi; Iwata, Seido; Kinugawa, Yoshikazu
Abstract: Pasteurella multocida, often found as part of the human oral flora and in finger/toenails, also exists in many animals, especially cats, dogs, and pigs. Although rare, pasteurella infection in neonates can cause serious systemic disease, such as meningitis. In this article, a 23‐day‐old girl presented with decreased appetite and irritability for >2 days. Eighteen days previously her pet cat had jumped onto the left side of her head while she was sleeping. On laboratory data C‐reactive protein was high, and on cerebrospinal fluid (CSF) analysis leukocyte count was extremely high, with low glucose and high protein. P. multocida grew out of the blood and CSF cultures, and she was successfully treated with antibiotics for 3 weeks. Although pasteurellosis rarely occurs, it can sometimes lead to life‐threatening situations, so parents should exercise caution when having pets around their children.